The Influence Of Intrinsic And Extrinsic Motivating Factors On Work Performance At Banking Sectors In Malaysia - Ravesangar, Kamalesh (2019)
Work performance is always essential to the development of a company to maintain its competitive advantage especially for banking sectors which operates to provide the best services to customers. The purpose of this study is to examine the influence of intrinsic and extrinsic motivating factors on work performance at banking sectors in Malaysia when the role of psychological ownership as mediator existed. This study was carried out to determine issues related to employees’ work performance based on poor service quality, work stress, lack of job knowledge, poor employee retention, inflexibility and poor communication in Malaysian banking sectors. The research instruments utilized in this study were personal administered and through online mail questionnaires. A total of 3700 questionnaires distributed among the front-line employees at conventional and Islamic banks in Malaysia but only 370 questionnaire are fit for the further analysis. The data of survey has been collected within one month duration and sample have been collected through cluster sampling. Based on the findings, only responsibility has significant positive influence on work performance. The next result also shows that personal growth, work condition and company policy have significant positive impact on psychological ownership. The following findings shows that psychological ownership positively mediates the relationship between both company policy and work condition with work performance.